Cost-effectiveness analysis of anaesthesia regimens for paediatric strabismus surgery based on multicentre retrospective cohort data from Japan - Soichiro Obara; Taiki Kojima; Yusuke Yamauchi; Takashi Fujiwara; Aya Sueda; Riku Takahashi (BJA Open)
Background: Postoperative vomiting (POV) after paediatric strabismus surgery poses both clinical and economic challenges. This study evaluates the cost-effectiveness of different anaesthesia regimens, focusing on the addition of ondansetron (OND), in preventing POV. Methods: A cost-effectiveness analysis was conducted from the perspective of a Japanese public healthcare payer using retrospective cohort data of children (aged 3–15 years) undergoing strabismus surgery at three institutions (February 2016–November 2023). The primary outcome measure was cost per averted POV (aPOV) within 24 hours post-surgery. Incremental cost-effectiveness ratios were calculated, and sensitivity analyses accounted for uncertainties. Results: A total of 2772 patients were included. Total intravenous anaesthesia (TIVA) regimens were compared, as OND was used only in TIVA regimens. The aPOV rate for TIVA with sub-Tenon block and dexamethasone (DEX) was 91.0%, whereas TIVA with sub-Tenon block, DEX, and OND had an aPOV rate of 96.3%. The incremental cost of adding OND was €21.2, resulting in an incremental cost-effectiveness ratio of €400.6 per aPOV. A sensitivity analysis showed OND cost was the most influential factor. The cost-effectiveness acceptability frontier showed the probability of cost-effectiveness for TIVA+DEX ranged from 0% to 97.4% for thresholds of €0–€200 per aPOV, whereas TIVA+DEX+OND raged from 0% to 9.3%, and TIVA only ranged from 100% to 0%. Conclusions: TIVA with DEX alone is the most cost-effective regimen for preventing POV in paediatric strabismus surgery in the current Japanese public healthcare system. The addition of OND in TIVA regimens may not be justified from the viewpoint of cost-effectiveness.